2019
DOI: 10.1002/ijc.32669
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to triage optimization in HPV primary screening: Extended genotyping and p16/Ki‐67 dual‐stained cytology—Retrospective insights from ATHENA

Abstract: The objective of our study was to assess the performance of different triage strategies for high‐risk human papillomavirus (hrHPV)‐positive results utilizing either extended genotyping or a p16/Ki‐67 dual‐stained cytology (DS) approach, with or without partial genotyping. A subset of women with hrHPV infections participating in the Addressing the Need for Advanced HPV Diagnostics (ATHENA) study were analyzed to determine the number of cervical intraepithelial neoplasia grade 3 or worse (≥CIN3) cases detected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
2
37
1
Order By: Relevance
“…But, HPV16/18 genotyping is useless for cervical cancer patients with hrHPV infections other than HPV16/18 subtypes. In our study, the sensitivity and specificity of HPV16/18 genotyping was 77% and 71%, respectively, to detect CIN2+, which is concordant with the data published by Bu et al from the Guangdong Province, China (sensitivity 65%, specificity 67%) 30 and other studies analyzing other populations 31,32 . Our study shows that the diagnostic performance of three methylation panels was noninferior to the HPV16/18 genotyping to triage hrHPV‐positive women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But, HPV16/18 genotyping is useless for cervical cancer patients with hrHPV infections other than HPV16/18 subtypes. In our study, the sensitivity and specificity of HPV16/18 genotyping was 77% and 71%, respectively, to detect CIN2+, which is concordant with the data published by Bu et al from the Guangdong Province, China (sensitivity 65%, specificity 67%) 30 and other studies analyzing other populations 31,32 . Our study shows that the diagnostic performance of three methylation panels was noninferior to the HPV16/18 genotyping to triage hrHPV‐positive women.…”
Section: Discussionsupporting
confidence: 91%
“…and other studies analyzing other populations. 31,32 Our study shows that the diagnostic performance of three methylation panels was noninferior to the HPV16/18 genotyping to triage hrHPV-positive women. For triaging hrHPV-positive women in China, one might consider cotesting of HPV16/18 genotyping and methylation analysis, especially the potential application of methylation panels in hrHPV infections other than HPV16/18.…”
Section: Discussionmentioning
confidence: 75%
“…The high prevalence of hrHPV not only leads to unnecessary colposcopy or follow-up burden [9], but also might add to the mental burden of the HPV-positive women [17]. However, in HPVbased screening programs, there is still no consensus on the optimal management of HPVpositive women to maximize disease detection and minimize colposcopy rates [18,19]. Risk stratification has important implications for the personalized risk management of HPV positive women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the most common screening method was high-risk HPV (hr-HPV) test. The superior sensitivity of clinically validated hr-HPV test and high repeatability with acceptable negative predictive value makes this method widely accepted as the most important strategy for the cervical cancer screening [6][7]. However, because of the unsatisfactory performance of hr-HPV test, the Preventive Services Task Force screening guidelines of the United States prefer primary hrHPV test every 5 years for screening [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another important screening tool is cytology based on the Papanicolaou (Pap) smear, which was in largescale use and reduced the cervical cancer incidence and mortality in many regions [7]. However, because of its low sensitivity for detecting cervical intraepithelial neoplasia grade 2 (CIN2) or higher lesion [4], clinicians prone to nd other effective tools to screen the cervical cancer, one of whic was p16/Ki-67 dual staining.…”
Section: Introductionmentioning
confidence: 99%